THE INFLUENCE OF WEBSITE CHARACTERISTICS, EXPERIENCE, CORPORATE IMAGE, AND TRUST, TOWARDS SATISFACTION ON JD.ID - Riski Stevanus Marijose Oroh; Deatri Arumsari Agung; Lena Ellitan (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2022)
The internet plays a vital role in the business environment. With the internet, companies can easily reach targeted consumers in a wide area and can deliver their services faster. This technology gives rise to high competition between companies in terms of delivery of goods and services using the internet as a means. Companies that can take full advantage of the internet may be able to dominate the market. Internet usage can be measured by how companies manage their websites, consumer experience, image, and consumer trust, which can lead to satisfaction. This study aims to analyze and understand the effect of website characteristics, consumer experience, and company image on consumer satisfaction mediated by trust in JD.ID. This study uses a quantitative method by distributing online questionnaires to the JD.ID user community, with a total of 150 respondents with a minimum age of 17 years, and domiciled in Surabaya. The results showed that website characteristics and consumer experience significantly affect consumer trust. Further, corporate image has a significant effect on trust, while consumer trust has a significant effect on consumer satisfaction. Moreover, consumer trust strongly mediates the relationship between website characteristics, consumer experience, and company image on consumer satisfaction. The result indicates that the higher the characteristics of the JD.ID website, consumer experience, company image, and consumer confidence in JD.ID, the higher the level of consumer satisfaction.